„OVER DERES EGEN RACES LIG“: Om Knud Rasmussens syn på kulturmødet og slægtskabet mellem grønlændere - Thisted, Kirsten (Tidsskriftet Antropologi, 2004)
In an article from 1920 Knud Rasmussen wrote: ”One has no choice. The life of all people of nature (“naturfolk” – the term Rasmussen prefered to “primitive people”) in the future is depending solely on their potentials for development under new conditions; the road to the future must lead over the dead body of their own race.” These words have later been quoted again and again, often detached from their context and therefore misunderstood. It is hard to make the statement match Knud Rasmussen’s role as the communicator of Inuit knowledge and the defender of “primitive” (aboriginal) people, and the statement is therefore usually explained away. The article presents the statement in its full context, including not only the whole series of articles in which it appeared, but also a central text from the Greenlandic part of Rasmussen’s writings. Generally, researchers have been occupied with Rasmussen’s bi-lingual and bi-cultural skills, but at the same time they have excluded the books written in Greenlandic from their research. Seen in the context of Knud Rasmussen’s (very successful) attempt to introduce the evolution-theory to the Greenlanders, there can be no doubt that Rasmussen did in fact mean, what he wrote. To Rasmussen, the future for the aboriginal people of Greenland lay in the interethnic relationship between Danes and Eskimos, which had resulted in a whole new race of people who were neither Eskimo (Inuit) nor Danes, but Kalaallit, Greenlanders. Read in its context, and seen also from the perspective of Rasmussen’s own time and personal situation, the statement might in fact not be so very deviant from the present time’s focus upon mixed identities and hybridity.